2007
DOI: 10.1101/lm.597507
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of muscarinic receptor blockade in prelimbic cortex on acquisition and memory formation of an odor-reward task

Abstract: The present experiments determined the consequences of blocking muscarinic cholinergic receptors of the prelimbic (PL) cortex in the acquisition and retention of an odor-reward associative task. Rats underwent a training test (five trials) and a 24-h retention test (two retention trials and two relearning trials). In the first experiment, rats were bilaterally infused with scopolamine (20 or 5 µg/site) prior to training. Although scopolamine rats showed acquisition equivalent to PBS-injected controls, they exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 62 publications
2
29
0
1
Order By: Relevance
“…In contrast, STFP performance was not affected when scopolamine was administered 1 h after training, suggesting that the cholinergic system in the prelimbic cortex is likely important for the acquisition and early consolidation of the task (Carballo-Márquez et al, 2007). Although it was reported that the quality of social interaction between the 'observer' and the 'demonstrator' was not different between sham-and scopolamine-treated animals and that olfaction was intact, other non-specific effects of scopolamine on learning and/or attention cannot be excluded (for further reading, see Klinkenberg and Blokland, 2010).…”
Section: Cortical Areas Involved In Social Learningmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, STFP performance was not affected when scopolamine was administered 1 h after training, suggesting that the cholinergic system in the prelimbic cortex is likely important for the acquisition and early consolidation of the task (Carballo-Márquez et al, 2007). Although it was reported that the quality of social interaction between the 'observer' and the 'demonstrator' was not different between sham-and scopolamine-treated animals and that olfaction was intact, other non-specific effects of scopolamine on learning and/or attention cannot be excluded (for further reading, see Klinkenberg and Blokland, 2010).…”
Section: Cortical Areas Involved In Social Learningmentioning
confidence: 77%
“…Infusion of the muscarinic cholinergic antagonist scopolamine into the prelimbic cortex of rats before or during training impaired STFP performance 24 h after the last training session Carballo-Márquez et al, 2007). In contrast, STFP performance was not affected when scopolamine was administered 1 h after training, suggesting that the cholinergic system in the prelimbic cortex is likely important for the acquisition and early consolidation of the task (Carballo-Márquez et al, 2007).…”
Section: Cortical Areas Involved In Social Learningmentioning
confidence: 99%
“…2A), in accordance with previously described procedures (Quiroz-Padilla, GuillazoBlanch, Vale-Martinez, Torras-Garcia & Marti-Nicolovius, 2007). The reinforcement (US, chocolate rice cereal placed at the bottom of the opening in the target sponge) was associated with the same odor across trials (CS + ), and the rewarded odor was randomly assigned to each rat in a counterbalanced manner.…”
Section: Acquisition Sessionmentioning
confidence: 99%
“…The training apparatus and behavioral procedures are explained elsewhere (Carballo-Marquez et al, 2007). The training apparatus was a 60 x 60 x 40cm square box containing three sponges (8.5 x 6.5 x 5.5cm) with a 3-cm diameter hole cut into the center to a depth of 2.5cm, placed in glass slide-holders of the same size.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation